Public Broadcasting Reform in the Transitional Society: The Case of Indonesia - Masduki, Masduki (JURNAL KOMUNIKASI INDONESIA, 2017)
The formal adoption of public service-oriented broadcasting (PSB) in countries undergoing political transition in Asia is increasing. However, this initiative is not protected by strong regulations. For instance, Indonesian PSB, which is represented by RRI (Radio of the Republicof Indonesia) and TVRI (Television of the Republic of Indonesia), remains difficult to realize. The arrival of universal ideas to establish PSB since two decades ago in the country lacks public engagement. Under a weak regulation, namely Broadcasting Law No. 32/2002, the PSB is far away from detailed preparations to serve as a truly public oriented broadcaster. This paper examines the process of formulating PSB bill within the Broadcasting Law, particularly its formation and public involvement in the law making process. This paper investigates why the outcome of the PSB law is that weak by observing how the policy was made. At the end, this paper recommends what could be done to improve the PSB Law to accelerate PSB institutional reform toward Public Service Media in Indonesia, particularly in the form of public engagement, both locally and globally within a framework of connected society. Adopsi formal Lembaga Penyiaran Publik (LPP) di negara dengan transisi politik di Asia semakin meningkat. Namun, inisiatif ini tidak terlindungi oleh peraturan yang kuat. Misalnya, LPP Indonesia yang diwakili oleh RRI (Radio Republik Indonesia) dan TVRI (Televisi Republik Indonesia) sulit dilaksanakan. Kemunculan gagasan universal untuk membangun LPP dalam dua dekade di negara ini adalah kurangnya keterlibatan publik. Di bawah peraturan yang lemah, yaitu UU Penyiaran 32/2002, LPP masih jauh dari persiapan yang matang dan penyiar yang benar-benar berorientasi pada masyarakat. Makalah ini membahas proses perumusan undang-undang LPP dalam UU Penyiaran, khususnya selama proses pembuatan dan keterlibatan publik dalam proses pembuatan kebijakan industri penyiaran. Tulisan ini menyelidiki mengapa hasil undang-undang LPP di Indonesia lemah dengan mengamati bagaimana kebijakan tersebut dibuat. Pada akhirnya, tulisan ini merekomendasikan tentang apa yang dapat dilakukan dalam memperbaiki undang-undang LPP untuk mempercepat reformasi kelembagaan LPP terhadap Media Pelayanan Publik di Indonesia, terutama dalam bentuk keterlibatan publik, baik lokal maupun global dalam kerangka masyarakat yang terkoneksi.